THE ANALYSIS OF STUDENT’S MISBEHAVIOR IN LEARNING ENGLISH LESSON - Puspitaloka, Nina; Syafitri, Intan Kurnia (Universitas Muhammadiyah Semarang, 2019)
Student’s misbehavior, sometimes, can interrupt the process of teaching and learning. Moreover, one of students didn’t realize that his/her misbehavior can hinder their achievement on English lesson. The purposes of this research are: (1) to find out the characteristics of student’s misbehavior, and (2) to find out the factor of student’s misbehavior in learning English lesson. The research used qualitative approach. The participants of this research were 20 students at SDN Cadaskertajaya 1 Karawang. The results of this research showed that: (1) there are three kinds of student’s misbehavior to English lesson, There are: (a) in-attention, for examples daydreaming, doodling and looking at the window; (b) disruption, for examples talking with friends, laughing in-appropriately and shouting out during instruction; (c) annoying others, for examples provoking, teasing, and calling names. (2) The factor of student’s misbehavior is affected by internal and external. The internal factor is students itself, for instances: attention seeking and learning difficulties. In other hand, the external factor is from the teacher and society.